Solitary cysticercosis of the sternocleidomastoid muscle. Issue 6 (8th June 2021) - Lal, Tusharindra; Paramasivam, Surendran; Jayapal, Badhrinath; Kataria, Riya
Abstract : Cysticercosis is a tropical infection caused by the larval form of Taenia solium and is usually known to affect the central nervous system. We report a young man who presented with a swelling in the neck and was treated with surgical excision and antihelminthics.